2021
DOI: 10.1002/csc2.20609
|View full text |Cite
|
Sign up to set email alerts
|

Coping with cold: Sorghum cold stress from germination to maturity

Abstract: Sorghum (Sorghum bicolor) is an important crop that is highly drought tolerant, but susceptible to low temperatures. Many studies have begun to explore the genetic basis of variation in chilling sensitivity in the sorghum germplasm in an effort to improve sorghum's chilling tolerance. However, differences in genetic maps and updates to the sorghum reference genome have made comparing studies of chilling in sorghum challenging. Here, we review the current state of research on chilling tolerance and susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Chilling stresses early in the growing season have been shown to affect metabolism and photosynthesis, including thylakoid electron transport, carbon assimilation, and stomatal control (Abbas, 2012; Bekele et al, 2014; Casto et al, 2021). Cold soil temperatures reduce root growth by reducing the availability of sugars and root development by initiating second and third-order laterals and inhibition of root elongation (Kaspar and Bland, 1992; Nagel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Chilling stresses early in the growing season have been shown to affect metabolism and photosynthesis, including thylakoid electron transport, carbon assimilation, and stomatal control (Abbas, 2012; Bekele et al, 2014; Casto et al, 2021). Cold soil temperatures reduce root growth by reducing the availability of sugars and root development by initiating second and third-order laterals and inhibition of root elongation (Kaspar and Bland, 1992; Nagel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In general, cold soil temperatures are known to limit root growth and branching by reducing the availability of sugars to the roots (Kaspar and Bland, 1992;Nagel et al, 2009), and increase the mean diameter of roots (Miyasaka and Grunes, 1990;Farooq et al, 2009;Hassan et al, 2021;Zhou et al, 2021). In sorghum, known effects of cold soil temperatures and chilling stresses early in the season include impaired metabolism and photosynthesis, carbon assimilation, and stomatal control (Abbas, 2012;Bekele et al, 2014;Casto et al, 2021). Low temperatures in the root meristems can also be expected to affect the production of growth substances, and or reduce the uptake of diffusion of nutrients such as potassium and phosphorus (Koevoets et al, 2016;Zhou et al, 2022).…”
Section: Root Growth and Functionmentioning
confidence: 99%
“…Several studies have shown that germinating seeds, particularly of tropical crops such as cotton [ 5 ], maize [ 6 ], sorghum [ 7 ] and rice [ 8 ], are highly sensitive to cold stress [ 9 ]. Imbibition of cold water induces excessive leakage of solutes, including amino acids and proteins that are conducive to pathogenic spore germination on seeds [ 10 ].…”
Section: Introductionmentioning
confidence: 99%